The Effect of Teacher Professionalism and Student Learning Motivation Through Blended Learning Model On Improving Student Learning Outcomes Of Class XI Vocational High School 1 Medan in The 2023/2024 Academic Year - Hasyim; Devita Rahmawati Napitupulu; Esty Pudyastuti (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
With the use of the blended learning model, this study attempts to assess the influence of student learning motivation and teacher professionalism on the learning outcomes of Grade 11 students at SMK Negeri 1 Medan in the academic year 2024–2025. This research, which was carried out at SMK Negeri 1 Medan, was motivated by the issues with employing less varied learning models and the lack of interest among students in studying. An Ex-Post Facto design was employed in the quantitative research methodology. 140 pupils from class XI OTKP SMK Negeri 1 Medan made up the sample, and 58 additional individuals were selected at random using the proportional random sampling technique. Questionnaires, documentation, and observation were used to gather data. Coefficient of determination, multiple linear regression, moderated regression analysis (MRA), simultaneous hypothesis testing (F-test), and partial hypothesis testing (T-test) are all used in data analysis. 1. The following conclusions were drawn from the research's findings: The blended learning strategy results in a significant and favorable improvement of 24.2% in learning outcomes. 2. Students that are motivated to learn achieve better learning outcomes by 15.7%. It has a significant and advantageous impact. 3.The professional development of teachers significantly mitigates the 2.3 percent effect of the blended learning learning paradigm on student learning outcomes. 4. At 2.4%, instructors' professionalism has a significant impact on students' enthusiasm to learn in respect to learning objectives. Overall, this study demonstrates that instructor professionalism dramatically modifies the 2.4% learning outcomes that students are motivated to learn.